Organizational Modes and Water Service Performance: A 1995–2025 Meta-Analysis and Implications for PPPs and Regional Multiservice Companies (SRMs) in Morocco - Mohamed Charaf Elouafai; Jalal Azegagh (European Scientific Journal, ESJ, 2026)
The organization of urban water services remains a contested issue in low- and middle-income countries, where public provision, delegated management, and hybrid arrangements coexist. In Morocco, the simultaneous presence of public régies, the national utility (ONEE), delegated public–private partnerships (PPPs), and newly established Regional Multiservice Companies (SRMs) raises persistent questions regarding the relative performance of alternative organizational modes. This study aims to assess whether and under what conditions different governance arrangements influence water service performance.Following the PRISMA protocol, a meta-analysis of 173 empirical studies published between 1995 and 2025 was conducted, yielding 742 effect sizes across six performance dimensions: efficiency, access, service quality, equity, environmental sustainability, and governance. Random-effects models and moderator analyses were used to examine the role of regulatory capacity, performance indicators, and benchmarking mechanisms.The results indicate that delegated management and PPPs are associated with higher efficiency outcomes (g ≈ 0.22) and modest improvements in access and service quality, while equity-related outcomes tend to be negative and environmental effects remain statistically weak. Performance gains are significantly conditioned by regulatory strength, the breadth of key performance indicators, and the presence of yardstick competition, suggesting that ownership structure alone does not determine outcomes.These findings have important policy implications for Morocco’s ongoing regionalization reform. The consolidation of water services under SRMs should be accompanied by transparent benchmarking frameworks and targeted social tariff mechanisms to reconcile efficiency objectives with social inclusion and long-term sustainability.